The Impact of Audit Technology on Audit Task Outcomes: Evidence for Technology‐Based Audit Techniques* - Eulerich, Marc; Masli, Adi; Pickerd, Jeffrey; Wood, David A. (Contemporary Accounting Research, 2023)
ABSTRACT As audit technology becomes more widespread, practice and academia are raising concerns about the costs and benefits of these technologies. We examine how internal auditors use technology‐based audit techniques (TBATs) and how TBATs impact the efficiency and effectiveness of their audits. We use two surveys and interviews of individual auditors and chief audit executives (CAE) to examine their perceptions of TBATs. Auditors perceive TBATs as beneficial. Specifically, an increase in the use of TBATs is associated with completing more audits, finding more risk factors, providing more recommendations, and decreasing audit days. However, CAEs also perceive TBATs to be costly. An increase in the use of TBATs is associated with an increase in the size of the internal audit function. Finally, interviews with CAEs suggest that TBATs are not used more often because of difficulties in quantifying their benefits, observing their benefits in a timely manner, and hiring auditors with appropriate skills. Overall, TBATs stand to increase the efficiency and effectiveness of audit tasks, but auditors struggle to quantify their net cost‐benefit tradeoff. Our findings validate the issues raised by both proponents and opponents of audit technologies and help provide empirical data to inform their decision‐making process regarding the future of these tools. Additionally, our study prompts several avenues for future research that can help inform regulators, practitioners, and researchers on how these technologies are impacting the auditing profession.